The Influence of Competence on Employee Performance at the Staffing Agency and Human Resource Development in Bone Regency - Rusnaedi Rusnaedi; Andi Asrijal; Mashuri Mashuri (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Employee competence in an organization is very decisive in achieving an organizational goal. The better the human resources in an organization, the more opportunities to achieve effective and efficient organizational goals will be realized. This research was carried out with the aim of knowing how competence influences employee performance at the Personnel Agency and Human Resource Development Agency Bone regency. The stages of the research method, starting from theoretical studies and empirical studies, preparation of proposals, testing the validity and reliability of instruments, data collection, analysis and discussion. The data analysis used is multiple linear regression analysis. The results of the study show that there is a strong relationship and a significant influence on Academic Knowledge, Expertise and Communication in influencing motivation, thereby increasing employee performance